PENGARUH RUANG TERBUKA HIJAU TERHADAP IKLIM MIKRO DAN KENYAMANAN TERMAL PADA 3 LOKASI DI KOTA MANADO - Mala, Yordan P.; Kalangi, J. I.; Saroinsong, F. B. (EUGENIA, 2018)
Microclimate is an important requirement for urban communities in creating outdoor thermal comfort. Micro climate as a benchmark in determining thermal comfort consists of 4 (four) elements which are, air temperature, air humidity, wind speed and solar radiation. Green open space area is one way to create comfortable micro climate for the community. The purpose of this study is to analyze microclimate and thermal comfort in 3 (three) green open spaces. The researcher used a purposive sampling method and chose the area with the same characteristics, namely UNSRAT Field, Tikala Field, and KONI Field. The results obtained were that the UNSRAT Field had the highest thermal comfort level with a percentage reaching 90% at 10:00 a.m. and 80% at 1:00 p.m. In addition, the micro climates in the three locations have differences, differences occur due to canopy area, tree species, plants, pavement type and building area around green open space.Keywords : microclimate, climate, open space, green open space